Phenotypic variation of root-system architecture under high P and low P conditions in potato (Solanum tuberosum L.) - Julian Kirchgesser; Mousumi Hazarika; Silvia Bachmann-Pfabe; Klaus J. Dehmer; Mareike Kavka; Ralf Uptmoor (BMC Plant Biology, 2023)
Abstract Background Phosphorus (P) is an essential macronutrient required for plant metabolism and growth. Its acquisition by plants depends on the availability of dissolved P in the rhizosphere and on the characteristics of P uptake mechanisms such as root-system architecture (RSA). Compared to other crops, potato (Solanum tuberosum L.) has a relatively poor P acquisition efficiency. This is mainly due to its shallow and sparsely branched root system, resulting in a rather limited exploitable soil volume. Information about potato genotypes with RSA traits suitable to improve adaptation to nutrient scarcity is quite rare. Aim of this study is to assess phenotypic variation of RSA in a potato diversity set and its reactions to P deficiency. Results Only one out of 22 RSA-traits showed a significant increase under low-P conditions. This indicates an overall negative effect of P scarcity on potato root growth. Differences among genotypes, however, were statistically significant for 21 traits, revealing a high variability in potato RSA. Using a principal component analysis (PCA), we were able to classify genotypes into three groups with regard to their root-system size. Genotypes with both small and large root systems reacted to low-P conditions by in- or decreasing their relative root-system size to medium, whereas genotypes with an intermediate root system size showed little to no changes. Conclusions We observed a huge variation in both the potato root system itself and its adaptation to P deficiency. This may enable the selection of potato genotypes with an improved root-zone exploitation. Eventually, these could be utilized to develop new cultivars adapted to low-P environments with better resource-use efficiencies.